Ефективність використання «Аретенцину-ПЕО» у профілактиці патології третьої стадії отелення - Якимюк, М.; Yakymiuk, M.; Заїченко, О.; Zaichenko, O.; Корейба, Людмила Володимирівна; Koreyba, Ludmila; Koreyba, L. V.; Koreyba, Lyudmila Volodymyrivna; Koreyba, L.; Koreiba, L. V.; Coregba, L. V. (Дніпропетровський ДАУ, 2004)
Одержані результати свідчать про ефективність застосування аретенцину, оскільки послідова стадія у дослідних корів (168±19,46 хв.) скоротилась на 35 % (Р < 0,05) порівняно з контрольними (228±26,95 хв.). The results obtained indicate the effectiveness of the use of arerencin, as the sequential stage in experimental cows (168 ± 19.46 min.) Was reduced by 35% (P <0.05) compared to control (228 ± 26.95 min.).
The effectiveness of the use of "Aretencin-PEO" in the prevention of pathology of the third stage of calving
Корейба Людмила Володимирівна https://orcid.org/0000-0002-8658-1779
Keywords: корови; cows; Аретенцин-ПЕО; Aretencin-PEO; затримання посліду; retention of manure; ускладнення родів; complications of parturition